Factors influencing children's dietary variety in Eastern Indonesia: A comprehensive national analysis - Prasetyo, Yoyok Bekti; Ika Wardojo, Sri Suryaningsih; Dwi Laksono, Agung (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Limited dietary diversity among children is a critical public health concern across Indonesia, with Eastern Indonesia facing the most severe nutritional challenges among children. Purpose: This study aims to identify factors influencing children's dietary diversity in Eastern Indonesia. Methods: A cross-sectional study design was employed, utilizing data from the 2017 Indonesia Demographic and Health Survey (n = 1,476). Dietary diversity was assessed using the dietary diversity score (DDS), categorized into adequate and inadequate levels. Results: Key sociodemographic factors associated with DDS included the number of children in the household, place of residence, economic status, breastfeeding practices, and vitamin A supplementation, with p-values of 0.007, <0.001, 0.001, <0.001, and <0.001, respectively. Children who were not breastfed were 0.5 times more likely to have inadequate DDS compared to those who were breastfed (95% CI: 0.36–0.67). Urban-dwelling families had a 0.7 times lower risk of inadequate DDS than rural counterparts (p = 0.026; 95% CI: 0.47–0.95). Additionally, children from low-income families were twice as likely to experience inadequate DDS compared to those from higher-income families (p = 0.012; 95% CI: 1.14–2.99). Conclusion: Rural residency, low income, lack of breastfeeding, and inadequate vitamin A supplementation significantly contribute to poor dietary diversity among children in Eastern Indonesia. These findings highlight the need for targeted government interventions to bridge gaps in maternal education, enhance healthcare access, and improve families' socioeconomic conditions, ultimately advancing child nutrition and health in the region.